Dynamic mechanism of crater formation induced by inclusion during intense pulsed ion beam irradiation. (September 2020) - Zhong, Haowen; Zhang, Jie; Shen, Jie; Liang, Guoying; Zhang, Shijian; Xu, Mofei; Yu, Xiao; Yan, Sha; Remnev, Gennady Efimovich; Le, Xiaoyun
Abstract: Crater is a general defect appeared on metallic target after intense pulsed ion beam (IPIB) treatment, which greatly limits the utilization and development of this technology. Understanding the mechanism of crater formation is of great significance for IPIB application. It is reported that inclusion in metallic target is associated with crater formation. In this work, the inclusions exposed to vacuum environment on target surface were found to lead to crater formation during 2.0 J/cm 2 IPIB irradiation via a positioning observation experiment on high speed steel. To investigate the dynamic mechanism of crater formation, thermal conduction model and laminar flow model were performed successively. The flow field analysis revealed that surface tension coefficient difference between molten inclusion and molten matrix is the primary reason to drive melt flow and generate crater. In the subsequent evolution of the crater, surface curvature also plays an important part. Highlights: Inclusions exposed on target surface can generate craters during irradiation. Surface tension coefficient difference is the dominate cause to crater formation. The morphology of crater is also affected by the change of surface curvature. The dimension of crater increases with the melting time of target surface.